Projeto de guichê de atendimento contextualizado pela Análise Ergonômica do Trabalho - Fontes, Andréa Regina Martins; Braatz, Daniel; Bertoncello, Dernival; Santos, Luciana de Mendonça; Menegon, Nilton Luiz (Revista Gestão da Produção Operações e Sistemas, 2006)
This paper is based on the results obtained in the design process for furniture conceived to theBrazilian Post Office counter clerk, in an ampler Ergonomics analysis project of the service rendered incommercial counters. Considering the social construction perspective in the project, the resulting devicearticulates the ergonomics logics, security, engineering, operational advertising and the disclosing conflict ofvalues and variables, which are expressed in the new counter service in terms of physical structure and use. Theresulting design indicates the conflict between the sales clerk and the regular clerk, consequence of thedichotomy between the public service versus market competition in an operational reality. The new design hasmade the work organization flexible, leaving a higher degree of freedom for the worker, in its operative way.Keywords: Design Study; Activity Analysis; Integration between Ergonomics and Design.